1999
DOI: 10.1128/jvi.73.1.270-280.1999
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus Comparison: Divergent Evolution on Two Continents

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is a recently described arterivirus responsible for disease in swine worldwide. Comparative sequence analysis of 3′-terminal structural genes of the single-stranded RNA viral genome revealed the presence of two genotypic classes of PRRSV, represented by the prototype North American and European strains, VR-2332 and Lelystad virus (LV), respectively. To better understand the evolution and pathogenicity of PRRSV, we obtained the 12,066-base 5′-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
410
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 633 publications
(422 citation statements)
references
References 67 publications
8
410
0
4
Order By: Relevance
“…Different pathogenic PRRSV strains in the field induced totally different consequences of infected pigs because of genetically extensive variation (Li et al, 2007;Meng, 2000;Nelsen et al, 1999). Our previous studies have shown that the low pathogenic PRRSV (LP-PRRSV) infection resulted in highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) infection pigs lung acute lung injury (ALI)…”
Section: Introductionmentioning
confidence: 99%
“…Different pathogenic PRRSV strains in the field induced totally different consequences of infected pigs because of genetically extensive variation (Li et al, 2007;Meng, 2000;Nelsen et al, 1999). Our previous studies have shown that the low pathogenic PRRSV (LP-PRRSV) infection resulted in highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) infection pigs lung acute lung injury (ALI)…”
Section: Introductionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome virus (PRRSV), a single-stranded, positive-sense RNA virus, is characterized by a high mutation rate with the potential of genetically diverse strains evolving over time (Forsberg et al, 2001;Hanada et al, 2005;Pirzadeh et al, 1998;Rowland et al, 1999). In the past, PRRSV isolates have emerged within the swine population with varying degrees of virulence (Fang et al, 2007;Han et al, 2006;Nelsen et al, 1999) possibly due to a high degree of mutation and recombination (Yuan et al, 1999(Yuan et al, , 2000(Yuan et al, , 2001(Yuan et al, , 2004. More recently, attention has focused on the occurrence of high mortality in Chinese swine herds which Veterinary Microbiology 158 (2012) To determine differences in infection kinetics of two temporally and genetically different type 2 porcine reproductive and respiratory syndrome virus (PRRSV) isolates in vivo with and without concurrent porcine circovirus (PCV) type 2a or 2b infection, 62 pigs were randomly assigned to one of seven groups: negative controls (n = 8); pigs coinfected with a 1992 PRRSV strain (VR-2385) and PCV2a (CoI-92-2a; n = 9), pigs coinfected with VR-2385 and PCV2b (CoI-92-2b; n = 9), pigs coinfected with a 2006 PRRSV strain (NC16845b) and PCV2a (CoI-06-2a; n = 9), pigs coinfected with NC16845b and PCV2b (CoI-06-2b; n = 9), pigs infected with VR-2385 (n = 9), and pigs infected with NC16845b (n = 9).…”
Section: Introductionmentioning
confidence: 99%
“…Isolate ATCC VR-2332 (American Type Culture Collection, Manassas, VA, USA; GenBank accession number PRU87392; Nelsen et al, 1999) was propagated in MARC-145 cells, as described in Hermann et al (2007). To prepare one lot of high-titered PRRSV sufficient to conduct all the replicates, the propagated virus was pooled and concentrated using a Prep/Scale spiral wound ultrafiltration module (Model CDUF 001 LH, Millipore, Billerica, MA, USA) such that approximately 2 l of supernatant was reduced to approximately 200 ml of virus stock.…”
Section: Source Of Airborne Pathogenmentioning
confidence: 99%